The demographic, clinical and forensic profile of offenders diagnosed with epilepsy referred to the Free State Psychiatric Complex Observation Unit in terms of section 77 and/or 78 of the Criminal Procedure Act 51 of 1977 - P J Marais; F JW Calitz; P HJJ van Rensburg; G Joubert (South African Journal of Psychiatry, 2011)
Introduction. Limited information regarding the relation between psychopathology associated with epilepsy, crime and the legal aspects thereof is available in South Africa.